FEATURES OF GOVERNMENT CONTROL OF ACTIVITY OF FINANCIAL MEDIATORS ARE IN UKRAINE - О. Cheberyako; A. Loboda (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
This paper is about main aspects of state regulation of banks and non-bank financial intermediaries' activity in Ukraine. The study gives an explanation of main features of regulatory authority as to activity of financial intermediaries. The place of self-regulatory organization in state regulation of financial intermediary's activity is determined.